Main Consequences of Prior Export Performance Results: an Exploratory Study of European Exporters - Lages, Luis Filipe (2019)
With the exception of the work of Lages and colleagues, the international marketing literature has been examining performance exclusively as a dependent variable. This exploratory study builds on this emerging body of literature to discuss the main outcomes of performance, as it is expressed through the perceptions of European export managers. According to the results of a cross-national study of Portuguese and British exporting firms, this paper indicates that the main consequences of previous performance results are: a) need to seek performance improvement as a result of bad performance, b) maintain strategy as a result of good performance, c) market diversification, d) focus on competition, e) product diversification, f) quality, and more attention to g) macro and h) micro factors. Future international marketing research is encouraged to investigate performance as an independent variable.